The Effect of the Implementation of Online Single Submission (OSS) on the Effectiveness of Business Licensing Programs in the Marine and Fisheries Sector at the Investment and One-Stop Integrated Service Agency of West Sumatra Province - Cindy Aulia; Syamsir Syamsir (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The implementation of Online Single Submission (OSS) has become an important component of digital public service reform in Indonesia, particularly in simplifying business licensing procedures. However, empirical research examining the influence of OSS implementation on the effectiveness of business licensing programs in the marine and fisheries sector remains limited. This study aims to analyze the effect of OSS implementation on the effectiveness of business licensing programs in the marine and fisheries sector at the Investment and One-Stop Integrated Service Agency of West Sumatra Province. A quantitative approach with an associative survey design was employed, involving 100 business actors selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression, t-test, and coefficient of determination with SPSS. The findings indicate that OSS implementation has a positive and significant effect on program effectiveness, with a regression coefficient of 0.610, a t-count value of 15.212, and a significance value of 0.000. The coefficient of determination shows that OSS implementation explains 70.2% of the variance in the effectiveness of business licensing programs. These findings suggest that digital licensing systems play a strategic role in improving service accessibility, procedural efficiency, and administrative effectiveness in the marine and fisheries sector. This study concludes that OSS contributes substantially to strengthening business licensing services in West Sumatra Province. The findings contribute to the literature on digital governance and public service effectiveness and provide practical implications for improving system stability, user literacy, service quality, and institutional coordination in digital licensing implementation.